DAMPAK AKUNTANSI NILAI WAJAR TERHADAP PEREKONOMIAN BANGSA - Dermawan, Elizabeth Sugiarto (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2012)
The fair value is expected to provide more relevant information to users. On the other hand, there are many controversial issues related to the application of fair value had been blamed for the global financial crisis. It is a trigger regulatory bodies to continue to monitor and evaluate the benefits of fair value in order not to create a conflict of interest between users of financial statements, which in turn could hurt the nation's economy.